2023
DOI: 10.1111/1365-2664.14396
|View full text |Cite
|
Sign up to set email alerts
|

Changes in trophic ecology of mobile predators in response to rainforest degradation

Abstract: Accelerating loss and degradation of tropical forests has led to a pressing need to understand the conservation value of remaining forests. Whereas most studies focus on the responses in community composition and taxonomic richness, more sensitive responses to habitat degradation are likely to be apparent through changes in the trophic complexity of generalist predators. Food web theory predicts that both trophic position and niche breadth of predators decrease with habitat degradation, with consequences for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our findings support our hypothesis that the isotopic niche of the stream consumer community would contract due to the reduced breadth of basal resources. Previous studies demonstrated that disturbances, such as degradation of forest quality and cover (Kemp et al, 2023), increased sedimentation (Burdon et al, 2020), and changes in the hydrological regime (Ru et al, 2020), could significantly alter food web characteristics, including the compression of the trophic niche.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support our hypothesis that the isotopic niche of the stream consumer community would contract due to the reduced breadth of basal resources. Previous studies demonstrated that disturbances, such as degradation of forest quality and cover (Kemp et al, 2023), increased sedimentation (Burdon et al, 2020), and changes in the hydrological regime (Ru et al, 2020), could significantly alter food web characteristics, including the compression of the trophic niche.…”
Section: Discussionmentioning
confidence: 99%
“…These research questions can be explored by examining changes to predator trophic structure, which summarizes functional diversity and species interactions within food webs (Abrams, 2018; Layman, Post, et al, 2007). Trophic structure determines both how predators respond to external resource inputs, and how they may distribute indirect effects to the rest of the terrestrial community (Kemp et al, 2023; Layman, Quattrochi, et al, 2007; Sabo & Power, 2002). Community‐wide estimates of trophic structure can be quantified and compared using the ratios of heavy to light carbon (δ 13 C) and nitrogen (δ 15 N) isotopes (Bearhop et al, 2004; Layman, Post, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen stable isotope ratios (δ 15 N) provide information about trophic position, whereas δ 13 C provides information about the basal food sources for upper trophic levels (Michener & Lajtha, 2008). Collectively, stable isotope ratios provide a time‐integrated measure of the total resource use of each consumer within a community, enabling the tracking of resource use in consumer diets and testing how trophic interactions are restructured by changing environmental conditions (Kemp et al, 2023; Nielsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pervasive land use change is among the primary causes of biodiversity loss and food web simplification, altering ecosystem functioning worldwide (Etard et al 2022;Kemp et al 2023;Moi et al 2023). The maintenance of healthy functioning ecosystems and high species diversity under increasing human pressure relies on food web rewiring and the ability of animals to shift their diet in disturbed ecosystems with scarce resources (Lu et al 2016;Kemp et al 2023).…”
mentioning
confidence: 99%
“…Pervasive land use change is among the primary causes of biodiversity loss and food web simplification, altering ecosystem functioning worldwide (Etard et al 2022;Kemp et al 2023;Moi et al 2023). The maintenance of healthy functioning ecosystems and high species diversity under increasing human pressure relies on food web rewiring and the ability of animals to shift their diet in disturbed ecosystems with scarce resources (Lu et al 2016;Kemp et al 2023). In this context, omnivores play a functional role in enhancing food web stability as adaptive foraging allows them to adjust their diet (Kratina et al 2012), facilitating their persistence in the face of humaninduced disturbances (Carvalho et al 2019).…”
mentioning
confidence: 99%